Perceptions on men's Likelihood to engage in Sexual Harassment - Kanny, Kamalasaravanan (2011)
Sexual harassment has always been a phenomenon that has been looked at many different dimensions by people all around the world. Due to this ambiguity, there have always been different perceptions of this subject. The aim of this study is to examine the factors associated with men’s likelihood to sexually harass. The study also would like to examine the relationship between familial factors, sex role perception, socio environment, organisation environment, men’s knowledge of sexual harassment with men’s likelihood to sexually harass. The study was carried out in 3 research universities in Klang Valley; namely Universiti Malaya, Universiti Kebangsaan Malaysia and Universiti Putra Malaysia. It involved 900 respondents in total, with a sample size of 300 respondents from 6 departments of each university. The researcher had used a two-tier sampling technique whereby, the first tier involves simple random sampling technique of identifying the 6 departments in each university. Later, a convenience sampling technique was used whereby, the researcher had approached the Head of Department of each department to select the 50 respondents of each of the 6 departments. Data was collected using a structured questionnaire distributed to men of all level of hierarchy in each university. The data was analysed using percentage, frequency, mean, standard deviation and bivariate analysis. Later, a regression analysis was carried out to determine the predictors that most strongly influence men’s likelihood to sexually harass. The results of the study show that besides familial factors which show there is insignificant relationship to men’s likelihood to sexually harass; other variables in this study : sex role perception, socio environment, organisation environment, men’s knowledge of sexual harassment all have significant relationship with men’s likelihood to sexually harass. The findings of this study also reveals that socio environment is the strongest predictor in influencing men’s likelihood to sexually harass followed by men’s knowledge of sexual harassment, sex role perception and lastly organisation environment. This study gives a new perspective in the research of sexual harassment and the findings reveals that consideration should be given to socio cultural models and gender ideology model in the design of interventions aimed at curbing this problem to further increase both at workplace and also in the community at large.